Macroeconomic policy and poverty - Iwan Azis (Asian Development Bank Institute (ADBI), 2008)
Slower growth and higher inflation can worsen poverty. By implication, maintaining macroeconomic stability is necessary to reduce poverty. When a typical aggregate demand (AD) policy for stabilization is not effective, however, its impact on poverty could be devastating as incomes of the poor typically decline with falling output. In this study, I argue that when poverty reduction is included in welfare objectives, it is imperative that policymakers weigh the impact of macroeconomic policy on the poverty line and household incomes. I address this issue by exploring the theoretical and empirical link between output, price, poverty line, and household incomes, and juxtapose them with their combined effect on poverty. Central to my argument is the premise that neither growth itself nor stability per se is the answer to poverty reduction. Applying a structural vector autoregression (SVAR) with the Blanchard-Quah (B-Q) restriction to the data of two Asian countries, Thailand and Indonesia, it was revealed that the aggregate supply (AS) curves in both countries are flat, implying that a stabilization policy based on AD shock is not effective. On the other hand, an AD expansion can produce non-inflationary growth and raise the incomes of the poor. To the extent that the transmission mechanism through which output affects household incomes is complex, involving direct, indirect, and feedback effects within an economy-wide system, a general equilibrium model with a detailed financial block was used. From the model simulations, poverty and income inequality results were found to be sensitive to the type of shock, price elasticity of wages, and structure of the economy, particularly the mechanisms by which the financial sector affects household income. While a positive fiscal shock tends to reduce poverty in Thailand, but not in Indonesia, the effect of an expansionary monetary policy on poverty can be either favorable or unfavorable. As shown in the Indonesia case, when the price elasticity of wages is low, the effect can be favorable but it can be unfavorable if the elasticity is high. An expansionary policy can raise the earnings of financial asset holders (i.e., higher income households) more than the incomes of the poor, as is the case in Indonesia, but not in Thailand. A fundamental gain from using the approach is to allow policymakers to measure the intensity of the trade-offs between growth, stability, and poverty, based upon which macroeconomic stability with lower poverty can be achieved.
Keywords: E52; I31; C68; G11; O1; 330; Armut; Konjunkturpolitik; Globalsteuerung; Thailand; Indonesien